Individuals recently abstinent from methamphetamine show selective cognitive and behavioral differences when compared to age-matched controls - Vest, M. Frances; Dumitrescu, Alexandru Mihai; Johnson, Matthew W.; Thompson, Elliot; Thomas, Alfred; Patterson, James C.; Murnane, Kevin S. (Frontiers in Psychiatry, 2025)
IntroductionSubstance use disorders are often associated with impairments in cognitive and behavioral processes. Methamphetamine use disorder (MUD), in particular, has been linked to such differences, though it remains unclear whether response inhibition (the inability to withhold prepotent responses), risk taking, or other constructs play more prominent roles. Understanding the specific contributions of these constructs is essential for tailoring interventions and improving outcomes for individuals with MUD. This study aimed to investigate both subdomains of impulsivity in individuals recently abstinent from methamphetamine.MethodsParticipants with MUD (n=29) recruited from 30-day residential treatment programs and age-matched controls (n =27) completed the Iowa Gambling Task (IGT) and Balloon Analogue Risk Task (BART) to assess risk taking and delay sensitivity, and the Stroop Color and Word Task (SCWT) and Stop Signal Task (SST) to assess response inhibition. Two-way multivariate analyses of covariance (MANCOVAs) were performed to determine group differences.ResultsAnalyses revealed no significant group differences in IGT net score (p=0.62) and BART average pumps (p=0.45). Conversely, significant differences emerged in as evidenced by longer stop signal reaction times (p < 0.01) and lower SCWT accuracy (p=0.03) in the MUD group compared to age-matched controls.DiscussionThese findings suggest that methamphetamine use disorder is associated with specific cognitive and behavioral abnormalities. Targeting these constructs in treatment may improve outcomes for individuals recovering from MUD.